MANAJEMEN SISWA DAN PENGELOLAAN KELAS DALAM PEMBELAJARAN ALQUR’AN DI PONDOK PESANTREN TAHFIDHIL QUR'AN SIROJUL 'ULUM - Novi Udhiyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Sirojul 'Ulum Tahfidhil Qur'an Islamic Boarding School is an institution thatspecifically educates students to become tahfidz Qur'an while still paying attentionto the effective management aspects of education. The application of studentmanagement and class management in learning the Qur'an is very important sothat the Qur'an learning process runs optimally. The Tahfidhil Qur'an program issystematically designed to ensure that students are able to memorize the Qur'anproperly and correctly. Students are encouraged to memorize the Quran in depthwith effective and structured methods. Muroja'ah activities and memorizationdeposits are carried out routinely to maintain the quality of students memorization.Student management is carried out through a tiered coaching system, dailysupervision, and the involvement of students in structured daily activities of theIslamic boarding school. Management of the tahfidz class is carried out by dividingmemorization groups, murojaah schedules, and teaching methods that emphasizediscipline, motivation, and individual approaches. The supporting factors forsuccess are the discipline of students, the commitment of teachers, and aconducive pesantren environment. The inhibiting factors include differences instudent abilities, boredom in memorizing, and limited teaching staff. Overall, theimplementation of student management and classroom management at the Sirojul'Ulum Tahfidhil Qur'an Islamic Boarding School went well and was able to create alearning atmosphere that supported the success of the tahfidz program.